Explanation
XIV, 346 p.
Keywords: For some years we have been conducting at the University of Haifa an interdisciplinary seminar on explanation in philosophy and psychology. We habitually begin the seminar with some philosophical reflections on explanation - an analysis of the concept and its metaphysical underpinnings. We discuss the various models and proceed to examine explanation in the setting of psychology. Thus, from the outset, we have focused not only on the concept itself but also on its application. The objective that we have set for the seminar, attended by students from both departments, Philosophy and Psychology, has been a critical understanding of the concept of explanation, its use and limitations. We were keen on deepening our understanding of the concept and on exploring its applications in fields of knowledge other than psychology. This was the motivation for convening an international conference on explanation and its application. The conference took place in the spring of 1998 under the auspices of the University of Haifa. The present book is the fruit of this meeting. The reader should note that the second part of the Introduction presents a detailed analytical account of the book. We hope that this overview will facilitate efficient use of the book by directing the reader's attention to those issues that might be of interest to him or her.